Hak Anak Mendapatkan Pendidikan dalam Keluarga Menurut Islam - Abdul Natsir; Fathur Rofi'i; Kholisotul Ma’rufah (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2024)
This study aims to determine the right to receive education according to Islam. This study is a literature study (library research), with a psychological approach. Data collection uses a documentation method in the form of notes, transcripts, books, newspapers, magazines and so on. Data analysis uses a descriptive method with Reflective Thinking, namely a combination of two deductive and inductive methods. The results of the study show that in Islam the family education system is seen as a determinant of a child's future. So parents play a very important role and become the first and foremost educators for children which is a right that must be obtained by a child. Education for children begins during the process of forming a family until a sakinah family is formed. From this sakinah family, pious and pious children will be born. Therefore, families must be able to choose the right educational methods and materials that will be given to children, so that the goals of children's education, especially in forming pious children and being able to face increasingly complex future challenges, can be maximally successful. Keywords: Children's Rights; Family Education; Islam